PERAN ROEPELIN DALAM MEMPERTAHANKAN EKSISTENSI PELAYARAN PERAHU PADA PERTENGAHAN PERTAMA ABAD KE-20 - Endang Susilowati (Jurnal Sejarah Citra Lekha, 2016)
Roepelin (Roekoen Pelayaran Indonesia) coordinated activities of the perahu shipping. This was done by organizing perahu shipping to get cargos, find a market for goods carried by members of the various ports, assist members in dealing with various seaport regulations, determine shipping line, and providing capital assistance in the form of soft loans to members who lack of capital for sailing and trade. Roepelin’s role has made perahu shipping still exist despite having to compete with modern marine transportation.